Pemanfaatan Limbah Ampas Kopi Menjadi Sabun Batang Organik Guna Meningkatkan Ekonomi Masyarakat Desa - Fitri Noviyanti; Anggi Liyandinny Purba; Manda Wulandari; Jesika Melina Simamora; Richard Tambunan; Fandra Dikhi Januardani; Rosintan Sipayung (Yayasan Cerdas Pedia Indonesia, 2025)
This community service project addresses the environmental degradation and economic stagnation in Batu Silangit Village caused by unmanaged spent coffee grounds. Historically, this waste contributes to methane emissions and soil toxicity. Therefore, this study implements a circular economy strategy by converting coffee residue into organic bar soap. The methodology utilizes Community Based Participatory Research (CBPR) combined with the